ANALISIS PENGARUH KNOWLEDGE MANAGEMENT DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN KOPERASI TELKOMSEL (KISEL) JAKARTA SELATAN - Sendianto, Sendianto; Saragih, Bambang Ermansyah (Sekolah Tinggi Manajemen IMMI, 2023)
This study aims to determine and analyze the effect of Knowledge Management and Job Satisfaction on the performance Telkomsel Cooperative Employees (KISEL) of SouthJakarta. The results of this study prove that the role of human resources in the organization isimportant for the survival and development of the organization. The method used is quantitative, respondents' answers to questionnaires related to Knowledge Management and Job Satisfaction on the Performance Telkomsel CooperativeEmployees (KISEL) of South Jakarta on average provide an overview that the observedvariables show things that are already good. From the results of the processing of thequestionnaire, it is known that from a total of 30 respondents. The questionnaire was madeusing a Likert scale. The analysis technique used includes multiple regression test,correlation test, determination test, partial hypothesis testing and simultaneous hypothesistesting and coefficient of determination test using SPSS 25. The results show that partiallyand simultaneously Knowledge Management and job satisfaction have a significant effect onEmployee Performance Telkomsel Cooperative (KISEL) South Jakarta.